The Impact of Sectorial FDI on Economic Growth in Central, Eastern and Southeastern Europe - Mite Miteski; Dijana Janevska Stefanova (National Bank of the Republic of Macedonia, 2017)
This paper investigates the effects of foreign direct investment inflows in the industrial, construction and services sectors on economic growth in a panel of sixteen Central, Eastern and Southeastern European CESEE countries using data of different time spans within the 1998-2013 period. The empirical results show that total FDI contributes positively to the growth in the analyzed countries. With regards to our main focus, the analysis of the decomposition of FDI finds that FDI in the industrial and services sectors has a positive and significant effect on economic growth, whereas FDI in the construction sector does not exert statistically significant growth-promoting effects.
Keywords: F21; F43; C23; O47; 330; Foreign direct investment; economic growth; industrial sector; construction sector; services sector